Effect sowing date and Nitrogen fertilization on growth plant Anethum graveolens L - Ali, Abdul- Ameer; Hamaza Mjbel, Manal (Al-Qadisiyah Journal of Pure Science, 2018)
A field experiment was conducted, University of AL-Qadisiya on 2010 2011– winter season, to study the effect of two planting dates (20/9 and 20/10 2000) and four levels of nitrogen fertilizer as urea (46% N) (0 , 40 , 80 , 120 Kg N / ha) and their interactions upon growth and volatile oil quantity and quality of Anthum gravcolens L Treatments were arranged according to the randomized complete Block Design as a factorial experiment with four replications. The results can be summarized as fallow: 1.The first planting date had significantly higher plants, greater number of branches. The increased levels of nitrogen fertilizer from 0 up to 120 Kg N / ha increased plant height and diameter of both stem, and branches . However, the plant height, number of branches, diameter of stem were not affected significantly by interaction. 2. The first planting date increased the number of flower panicles per plant, number of fruits per panicles. Nitrogen fertilization at (40 Kg N / ha) increased the values of these characteristics significantly . 3. The results show that the first planting date gave higher oil percentage compared with second planting date, where as the second planting date. Nitrogen fertilization with 40 Kg N / ha gave significantly better increment in oil percentage. Results also showed that the interaction had significant effect upon oil percentage.